Appropriate use of tocilizumab in COVID-19 infection. (October 2020) - Keske, Şiran; Tekin, Süda; Sait, Bilgin; İrkören, Pelin and Kapmaz, Mahir and Çimen, Cansu and Uğur, Semra and Çelebi, İrfan and Bakır, Veli Oğuzalp and Palaoğlu, Erhan and Şentürk, Evren and Çağlayan, Benan and Çakar, Nahit and Tabak, Levent and Ergönül, Önder
Highlights: Earlier use of tocilizumab in COVID-19 infection is beneficial for survival, length of hospitalization and duration of oxygen support Administration of tocilizumab is based on an increase in requirements of oxygen support, progression of thoracic CT, elevation of inflammation IL-6, CRP, ferritin, d -dimer, and decrease in % lymphocytes Among the inflammation parameters, the earliest changes were detected at the levels of CRP, IL-6 and % lymphocytes Abstract: Objective: This study aimed to describe the effectiveness and optimum use of tocilizumab (TCZ) treatment by the support of clinical, laboratory and radiologic observations. Methods: All patients were followed up in the hospital with daily interleukin-6 (IL-6), C-reactive protein (CRP), ferritin, d -dimer, full blood count, and procalcitonin. Thoracic computed tomography (CT) was performed on admission, when oxygen support was necessary, and seven days after TCZ started. Disease course of the patients was grouped as severe or critical, according to their clinical, laboratory and radiologic evaluations. Results: Forty-three patients were included: 70% were male; the median age was 64 years (minimum–maximum: 27–94); and six (14%) patients died. The median duration of oxygen support before the onset of TCZ was shorter among the severe patient group than the critical patient group (1 vs. 4 days, p < 0.001). Three cases of 21 (14%) who received TCZ in the ward were transferred to ICU, and none of them died. The levels of IL-6, CRP, ferritin, d -dimer, and procalcitonin were significantly lower in the severe cases group than the critical cases group ( p = 0.025, p = 0.002, p = 0.008, p = 0.002, and p = 0.001, respectively). Radiological improvement was observed in severe cases on the seventh day of TCZ. Secondary bacterial infection was detected in 41% of critical cases, but none of the severe ones. Conclusion: Earlier use of TCZ in COVID-19 infection was beneficial for survival, length of hospitalization and duration of oxygen support. The recommendation for administration of TCZ was based on an increase in requirement of oxygen support, progression in thoracic CT, and elevation of inflammation markers, including IL-6, CRP, ferritin, and d -dimer, and decrease in % lymphocytes.